Comparative reconstruction of the predatory feeding structures of the polyphenic nematode Pristionchus pacificus. Issue 1 (3rd March 2022) - Harry, Clayton J.; Messar, Sonia M.; Ragsdale, Erik J.
Abstract: Pristionchus pacificus is a nematode model for the developmental genetics of morphological polyphenism, especially at the level of individual cells. Morphological polyphenism in this species includes an evolutionary novelty, moveable teeth, which have enabled predatory feeding in this species and others in its family (Diplogastridae). From transmission electron micrographs of serial thin sections through an adult hermaphrodite of P. pacificus, we three‐dimensionally reconstructed all epithelial and myoepithelial cells and syncytia, corresponding to 74 nuclei, of its face, mouth, and pharynx. We found that the epithelia that produce the predatory morphology of P. pacificus are identical to Caenorhabditis elegans in the number of cell classes and nuclei. However, differences in cell form, spatial relationships, and nucleus position correlate with gross morphological differences from C. elegans and outgroups. Moreover, we identified fine‐structural features, especially in the anteriormost pharyngeal muscles, that underlie the conspicuous, left‐right asymmetry that characterizes the P. pacificus feeding apparatus. Our reconstruction provides an anatomical map for studying the genetics of polyphenism, feeding behavior, and the development of novel form in a satellite model to C. elegans . Abstract : The novel morphology of a nematode model for the developmental genetics of polyphenism ( Pristionchus pacificus ) was reconstructed at the level of individual cells. A comparative study of this anatomical map revealed that the dimorphic, predatory morphology of P. pacificus shows, with respect to close outgroups lacking that morphology, complete conservation in the number of homologous cell classes and nuclei. Despite this conservation, new arrangements and taxonomically unique asymmetries were found to underlie a gross divergence in form. Highlights: All cells making the dimorphic, novel form of an animal with cell constancy were identified. Although the number of cells is fully conserved, divergence in form and connectivity—including fixed asymmetries—sheds light on the origins of this trait.